2012
DOI: 10.1021/ac203079c
|View full text |Cite
|
Sign up to set email alerts
|

NanoHPLC-nanoESI+-MS/MS Quantitation of Bis-N7-Guanine DNA–DNA Cross-Links in Tissues of B6C3F1 Mice Exposed to subppm Levels of 1,3-Butadiene

Abstract: 1,3-butadiene (BD) is an important industrial chemical and a common environmental pollutant present in urban air. BD is classified as a human carcinogen based on epidemiological evidence for an increased incidence of leukemia in workers occupationally exposed to BD and its potent carcinogenicity in laboratory mice. A diepoxide metabolite of BD, 1,2,3,4-diepoxybutane (DEB), is considered the ultimate carcinogenic species of BD due to its ability to form genotoxic DNA-DNA cross-links. We have previously employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…To achieve detection limits in the low fmol to amol range (1 per 10 8 –1 per 10 9 nucleotides) as required for our in vivo studies, we employed nanoLC/ESI + -HRMS 3 methodology on an Orbitrap Velos mass spectrometer. We and others have recently reported the use of high resolution mass spectrometry for DNA adduct analysis in complex samples and have shown that it dramatically reduces the matrix background, leading to greatly improved signal to noise ratios [37, 45, 46]. …”
Section: Resultsmentioning
confidence: 99%
“…To achieve detection limits in the low fmol to amol range (1 per 10 8 –1 per 10 9 nucleotides) as required for our in vivo studies, we employed nanoLC/ESI + -HRMS 3 methodology on an Orbitrap Velos mass spectrometer. We and others have recently reported the use of high resolution mass spectrometry for DNA adduct analysis in complex samples and have shown that it dramatically reduces the matrix background, leading to greatly improved signal to noise ratios [37, 45, 46]. …”
Section: Resultsmentioning
confidence: 99%
“…3438 These adducts represent the biologically relevant carcinogen dose following exposure to BD, and appear to correlate with cancer development in experimental animal models. 12,35 We recently reported mass-spectrometry based quantitation of N-7-(1-hydroxy-3-buten-2-yl) guanine (EB-GII) adducts induced by EB (a major genotoxic metabolite of BD) in DNA isolated from peripheral blood leukocytes of smokers, nonsmokers and occupationally exposed BD workers.…”
Section: Discussionmentioning
confidence: 99%
“…63 The LOD value of the method was 0.5 fmol/100 μg DNA, and the LOQ is 1.0 fmol/100 μg DNA, making it possible to quantify bis -N7G-BD adducts present at concentrations of 3 per 10 9 nucleotides. Using this methodology, bis -N7G-BD was quantified in tissues of laboratory mice treated with low ppm and sub-ppm concentrations of BD.…”
Section: New Analytical Approaches For Dna Adduct Analysismentioning
confidence: 97%
“…24 More recently, we reported nanoHPLC-nanoMS analysis of bis -N7G-BD in tissues of mice treated with sub-ppm concentrations of BD that approach occupational exposure limits. 63 …”
Section: Recent Examples Of Hplc-esi-ms/ms Analyses Of Dna Adductsmentioning
confidence: 99%